115,000 Miles and Counting: Extraordinary Athletic Activity After a Historic Total HipArthroplasty with 39-year Follow-up - Marguerite L. Gilmore, BA; Ansab Khwaja, MD; Daniel H. Wiznia, MD; Lee E. Rubin, MD (Arthroplasty Today)
We present an 81-year-old male who underwent a direct anterior approach total hip arthroplasty (THA) with a ceramic-on-ceramic bearing in 1986. Amazingly, the patient kept meticulous logbooks of his many athletic endeavors, which were tallied after 35 years in 2020. These included 20,797 miles of running, 2323 miles of swimming, 66,349 miles of bicycling, and at least 25,500 miles of walking, amounting to more than 114,969 miles of physical activity. As the average age of patients who undergo index THA decreases, the debate regarding physical activity recommendations after THA has become increasingly relevant for patients, but this topic is inadequately studied and thus remains an unanswered question.